Detection of Low Hydrostatic Pressure Using Fiber Bragg Grating Sensor - Naufal Aiman Madani; Retno Wigajatri Purnamaningsih; Nji Raden Poespawati; Maratul Hamidah; Sasono Rahardjo; Dena Karunianto Wibowo (International Journal of Technology, 2023)
The aim of this study was to investigate the detection of low hydrostatic pressure, serving as the foundation for developing an underwater pressure sensor. This included creating a single-mode, uniformly structured Fiber Bragg Grating (FBG) with a stainless-steel coating. The experiment included loading the sensor with different volumes of fresh water ranging from 0 ml to 6 ml, in increments of 0.25 ml, in the perpendicular vertical direction. This volume range corresponded to hydrostatic pressures ranging from 0 Pa to 40.55 Pa. The experimental results showed a consistent linear relationship between low hydrostatic pressure and Bragg wavelength, implying a sensitivity of 0.8092 pm/Pa, according to theoretical expectations. Subsequently, mathematical simulations were conducted based on the results to predict the sensor performance under various potential seabed temperatures. The simulation results indicated that as the temperature rose, there was a corresponding increase in the reflected wavelength difference by 5.3754 ×10-9 nm/Pa for every 1°C increase in seawater temperature.